Balok Beton Bertulang yang Diperkuat dengan Carbon Fiber Reinforced Polymer Wrap saat Dibebani Beban Gravitasi - Brian Widyan Hadi; Henricus Priyosulistyo; Muhammad Fauzie Siswanto (Universitas Negeri Yogyakarta, 2021)
ABSTRACTInnovation is developed continuously to find an optimal method of strengthening structural components. There are many strengthening methods for reinforced concrete structures. Carbon Fiber Reinforced Polymer Wrap as a flexural strengthening material according to ACI 440.2R was chosen. The research includes gravity load (dead load and live load) as the initial load during test according to SNI 2847-2013 chapter 20. This research examines the strength of the intact beam, strengthened reinforced beam, and failure pattern, respectively, compared to the intact beam's result theoretically and experimentally. The failure test results show that the maximum loads of the experiment beam were similar to the theoretical analysis with a ratio of 0.98 to 1.33. The failure patterns are shear, flexure-shear, spalling and diagonal cracks, and debonding failures. CFRPW can increase the strength and stiffness of the beams. The increase of CFRP beams (BF A and BF B) is 35,27% and 46,24%, respectively. The increase of stiffness ratio of BF A and BF B is 3,48 and 6,62 compared to BK 1. ABSTRAKSebuah inovasi yang terus dikembangkan agar menemukan sebuah metode yang optimal dalam perkuatan komponen struktur balok. Perkuatan balok beton bertulang dapat dilakukan dalam beberapa metode. Carbon Fiber Reinforced Polymer Wrap dipilih sebagai bahan penguat lentur sesuai ACI 440.2R. Penelitian ini meliputi beban gravitasi (beban mati dan beban hidup) sebagai beban awal pada saat pengujian sesuai SNI 2847-2013 pasal 20. Penelitian ini mengkaji kekuatan balok murni, kekuatan balok yang telah diperkuat, pola keruntuhan dan perbandingan antara hasil teoritis dan eksperimental. Hasil pengujian ultimit menunjukkan bahwa balok uji serupa dengan analisis teoritis dengan perbandingan beban maksimum 0,98 dan 1,33. Pola kegagalan adalah retak geser, geser lentur, keretakan spalling dan diagonal serta kegagalan debounding. CFRPW dapat meningkatkan kekuatan dan kekakuan balok. Peningkatan kekuatan BF A 35,27% dan BF B 46,24% terhadap BK 1. Peningkatan rasio kekakuan balok BF A dan BF B bila dibandingkan dengan BK 1 adalah 3,48 dan 6,62.